New remains and considerations on Nothrotheriidae from the late Pleistocene of La Ribera, Santa Fe, Argentina - Brambilla, Luciano (2019)
The remains of Nothrotheriidae are very scarce in the fossil record of the Pleistocene of Argentina but the locality La Ribera (late Pleistocene) has an unexpected concentration of members of this family. In this work, an astragalus and a femur assignable to Nothrotheriidae from La Ribera are described as Nothropus cf. carcaranensis Bordas, 1942. Other material of this family of sloths from this locality, among which is the holotype of Nothropus carcaranensis, are reviewed with discussion about the intraspecific variation of the femora. The elements studied herein provide a better understanding of the diversity of the Nothrotheriidae in Argentina.